BIMBINGAN DAN KONSELING PERAN ORANG TUA DALAM MENDIDIK ANAK YANG MALAS BELAJAR DALAM LINGKUNGAN SEKOLAH - Sukatin; Anisa Aulia; Salsa Billa Noprianita; Kanaya Mayruvaelni; Diana Putri Ningsih; Sukma Aulia (JIPDAS (Jurnal Ilmiah Pendidikan Dasar), 2025)
Laziness to learn in children is a common educational problem and can hinder academic development and character formation. Low learning motivation is not only influenced by internal factors of the child, but also by external factors, especially the family environment. In this case, parents have a very important role as primary educators who are responsible for instilling learning habits from an early age. This study aims to determine and describe the role of parents in educating children who are lazy to learn and the efforts made to increase children's motivation and interest in learning. This study used a qualitative approach with descriptive methods. The subjects consisted of parents and school-age children. Data collection techniques included observation, interviews, and documentation. The data obtained were then analyzed using data reduction, data presentation, and conclusion drawing techniques to obtain a comprehensive picture of parents' role in addressing children's laziness in studying. Research results show that parents play a significant role in shaping children's learning habits and motivation. This role includes providing motivation and advice, providing study support at home, monitoring the use of study and play time, and creating a comfortable and conducive learning environment. Furthermore, attentive parenting, effective communication, and the provision of educational rewards and sanctions contribute to fostering children's enthusiasm for learning. Therefore, consistent, active parental involvement can reduce laziness and encourage children to take greater responsibility for their learning.